PEMANFAATAN TEKNOLOGI DIGITAL DALAM PENGELOLAAN DAN DISEMINASI SUMBER DAYA INFORMASI BUDAYA - Clara Milensen; Ahmad Wahidi (2025)
This research examines the urgency and effectiveness of utilizing digital technology in the management and dissemination of cultural information resources (CIR). CIR forms the foundation of a society's identity, encompassing both physical artifacts and intangible expressions. The digital era offers significant potential for the preservation, accessibility, education, and efficient management of CIR through digitalization and online platforms. However, there is a significant gap between this potential and optimal implementation, evident in technical-managerial issues, low public information literacy, lack of data standardization, limitations in multidisciplinary human resources, financial sustainability challenges, and minimal community participation. Through a preliminary study in Palembang, it was found that despite its rich CIR, the city still faces data fragmentation and suboptimal integration. Therefore, this research aims to formulate a comprehensive strategy involving human resource development, adoption of global standards, creation of interactive platforms, and cross-sector collaboration to ensure effective and sustainable CIR management and dissemination, in order to inspire and educate future generations.